2017
DOI: 10.1590/1807-1929/agriambi.v21n5p327-332
|View full text |Cite
|
Sign up to set email alerts
|

Induced changes in the growth of four plant species due to lead toxicity

Abstract: A B S T R A C TLead is a toxic metal that affects plant growth and the ecosystem. This study evaluated the lead (Pb) bioaccumulation potential of vetiver (Vetiveria zizanioides L.), sunflower (Helianthus annuus L.), elephant ear (Alocasia macrorrhiza) and 'embaúba' (Cecropia sp.). The plant species were tested in a 50% nutrient solution -Hoagland and Arnon, constantly aerated, containing five Pb concentrations: 0, 50, 100, 200 and 400 mg L ). Pb concentration of up to 100 and 50.9 mg L -1 stimulated sunflower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…The presence of Pb elicits many stress symptoms in plants, including growth inhibition, which is considered most indicative of Pb-induced toxicity as well as one of the most important agricultural indices of heavy metal tolerance (Nareshkumar et al 2015). In the present study, Pb treatment reduced plant growth and overall biomass production of L. sativus, similar to previous results in other plant species (Batista et al 2017). Moreover, Pb can directly affect cell elongation by inhibiting cell wall enzymes and the plasmalemma ATPase by dampening electron translocation during photosynthesis and respiration, thus reducing plant growth (Zaefarian et al 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The presence of Pb elicits many stress symptoms in plants, including growth inhibition, which is considered most indicative of Pb-induced toxicity as well as one of the most important agricultural indices of heavy metal tolerance (Nareshkumar et al 2015). In the present study, Pb treatment reduced plant growth and overall biomass production of L. sativus, similar to previous results in other plant species (Batista et al 2017). Moreover, Pb can directly affect cell elongation by inhibiting cell wall enzymes and the plasmalemma ATPase by dampening electron translocation during photosynthesis and respiration, thus reducing plant growth (Zaefarian et al 2012).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, Pb treatment reduced plant growth and overall biomass production of L. sativus , similar to previous results in other plant species (Batista et al . ). Moreover, Pb can directly affect cell elongation by inhibiting cell wall enzymes and the plasmalemma ATPase by dampening electron translocation during photosynthesis and respiration, thus reducing plant growth (Zaefarian et al .…”
Section: Discussionmentioning
confidence: 97%
“…Batista et al evaluated the Pb bioaccumulation potential of four plant species including embaúba (Cecropia sp. ); however, none of the evaluated species met the hyperaccumulator criterion [42]. Rossato et al evaluated the effects of lead on the growth, lead accumulation and physiological responses of Pluchea sagittalis, and concluded that this species is Pb-tolerant, being able to accumulate on average 6730 and 550 µg Pb g −1 dry weight, respectively, in the roots and shoot, a physiological trait which may be exploited for the phytoremediation of contaminated soils and waters [43].…”
Section: Resultsmentioning
confidence: 99%
“…Plants can be classified as accumulators, excluders and indicators according to the bioaccumulation factor, taking into consideration the capacity to accumulate heavy metals (Ma et al 2001). Phytoremediation efficiency is evaluated by bioaccumulation factors of metals in different plant tissues and is used in several phytoremediation studies in hydroponic systems such as Batista et al (2017) in the phytoremediation of Pb or in the environmental impact assessment in areas contaminated by multiple metals, as in the research conducted by Boechat et al (2016a;2016b).…”
Section: Resultsmentioning
confidence: 99%